Preferencje wyborcze społeczeństwa zachodniopomorskiego w III RP - Chrobak, Piotr (My University, 2010)
W pracy doktorskiej analizując poszczególne wybory w III RP (zwłaszcza samorządowe) można wyróżnić dwa okresy: 1990-1998 – do reformy administracji publicznej oraz z lat 1999-2007. Wyniki wyborów od 1990 r. w regionie wskazują, że do 2005 r. silną pozycję polityczną miały tu ugrupowania lewicowe. Aby wykazać co powodowało, iż społeczeństwo regionu przez wiele lat wierne było partiom lewicowym, a następnie zaufało ugrupowaniom postsolidarnościowym, dokonano analizy programów i aktywności poszczególnych partii w regionie oraz analizy wyników wyborów prezydenckich, parlamentarnych i samorządowych.W celu dokładniejszej analizy starano się przebadać omawiany region również pod względem przemian społeczno-politycznych zachodzących w latach 1945-1989. Doświadczenia dotyczące wyborów z okresu Polski Ludowej mimo swej fasadowości miały pewien wpływ na postawę wyborców w III RP.Założono, iż dzięki wynikom powyższych badań, możliwa stanie się odpowiedź na pytanie w jaki sposób ukształtowały się preferencje polityczne mieszkańców regionu oraz w jakim kierunku i dlaczego nastąpiła ich zmiana. Celem badań było również wykazanie - oprócz dokonań władz samorządowych i środowisk opiniotwórczych regionu - aktywności działań władz centralnych wobec Pomorza Zachodniego, aby uzyskać odpowiedz na pytanie, w jakim stopniu sytuacja ogólnokrajowa mogła mieć wpływ na zmianę poglądów wyborców regionu.

In the doctoral thesis by analyzing particular elections in the third Republic of Poland (especially elections for a local government) two periods may be distinguished: 1990-1998 – until the reform of the public administration, and 1999-2007. The results of the elections in the region, which have been conducted since 1990, show that until 2005 left-wing parties had a very strong position. In order to show what has been the reason for the West Pomeranian community to support left-wing parties, and then place its confidence in post-solidarity parties, the author had to analyze not only the programs and activity of every political party in the region, but also the results of presidential, parliamentarian and local authorities’ elections. To make it more precise, attempts were made to analyze the region also with regard to socio-political changes that occurred between 1945 and 1989. Despite the superficiality of the People’s Republic of Poland, the experience of the elections during that time has had some influence on the voters. It has been assumed that due to the results mentioned above, the answer to a question of how the political preferences have shaped the electoral preferences of local people, and into which direction and why has this change occurred. What is more, besides of the achievements of the local authorities and people responsible for creating public opinion, the other aim of this research was to show the activity of central government towards the West Pomerania region. It was supposed to provide an answer to the question of to what degree the nationwide situation could have influenced the change in West Pomeranian voters’ views.
West Pomeranian community’s electoral preferences in the third Republic of Poland
Wydział Nauk Politycznych i Dziennikarstwa
Keywords: Pomorze; Pomerania; Partie polityczne; Political parties; Samorząd terytorialny; Local government; Marketing polityczny; Political marketing; Media